Components of Successful Spiritual Care - Sager, Elizabeth (Journal of religion and health, 2022)
The quantifiable health benefits of spiritual practice and religious community have inspired a movement toward addressing religion within health care and medical education, yet biomedical professionals still often avoid this topic (Giordano and Engebretson in Explore 2(3):216--225, 2006; Post et al. in Ann Intern Med 132(7):578, 2000). This is largely due to a lack of clarity on how to ethically engage with diverse spiritual practices and maintain professional boundaries regarding spiritual care. However, a majority of patients desire increased incorporation of spirituality in medical discussions, indicating a deficit in care that must be addressed (Best et al. in Patient Educ Couns 98(11):1320-1328, 2015; Zaidi in AMA J Ethics 20(7), 2018). In this article, I clarify what constitutes successful spiritual care by identifying its key components and major challenges. I then make recommendations for ethically mindful, comprehensive spiritual care and consider potential next steps including structural changes that prioritize compassion and empathy in medicine.